2017
DOI: 10.1038/srep42270
|View full text |Cite
|
Sign up to set email alerts
|

Neuronally-directed effects of RXR activation in a mouse model of Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is characterized by extensive neuron loss that accompanies profound impairments in memory and cognition. We examined the neuronally directed effects of the retinoid X receptor agonist bexarotene in an aggressive model of AD. We report that a two week treatment of 3.5 month old 5XFAD mice with bexarotene resulted in the clearance of intraneuronal amyloid deposits. Importantly, neuronal loss was attenuated by 44% in the subiculum in mice 4 months of age and 18% in layer V of the cortex i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 62 publications
(122 reference statements)
8
75
1
Order By: Relevance
“…We chose to examine memory functions of APP/PS1‐mice with the hippocampus‐dependent memory test 1 day after contextual fear conditioning as described before (Kimura & Ohno, ; Mariani et al, ). The mice were 12 months old at the time of experiment to ensure that they have fully developed amyloid pathology (Garcia‐Alloza et al, ; Jackson et al, ; Jankowsky et al, ; Kamphuis et al, ) and memory impairments typically observed in the strain (Kilgore et al, ; Lalonde, Kim, Maxwell, & Fukuchi, ; Minkeviciene et al, ; Volianskis, Kostner, Molgaard, Hass, & Jensen, ).…”
Section: Methodsmentioning
confidence: 99%
“…We chose to examine memory functions of APP/PS1‐mice with the hippocampus‐dependent memory test 1 day after contextual fear conditioning as described before (Kimura & Ohno, ; Mariani et al, ). The mice were 12 months old at the time of experiment to ensure that they have fully developed amyloid pathology (Garcia‐Alloza et al, ; Jackson et al, ; Jankowsky et al, ; Kamphuis et al, ) and memory impairments typically observed in the strain (Kilgore et al, ; Lalonde, Kim, Maxwell, & Fukuchi, ; Minkeviciene et al, ; Volianskis, Kostner, Molgaard, Hass, & Jensen, ).…”
Section: Methodsmentioning
confidence: 99%
“…The two times higher PPAR-α expression in males versus females could be responsible for the improvement of synaptic plasticity in male cognition-impaired mice by pemafibrate. PPARs and RXR receptors activation upregulates the expression of several synaptic related genes coding proteins engaged in excitatory neurotransmission [12,36]. Probably through these mechanism agonists of PPAR-α may have a promising effect in a mouse model of aging-dependent cognitive impairments [37,38].…”
Section: Ppar-α and Its Role In Neurotransmission In The Brainmentioning
confidence: 99%
“…Changes in ETV1 expression have likewise been linked with cognitive decline (Abe et al, 2011;Ding et al, 2016). RXR agonists that increase binding to the RXR motif have been shown to enhance synaptic density and improve cognitive function in mouse models of aging and Alzheimer's disease (Cramer et al, 2012;Nam et al, 2016;Tachibana et al, 2016;Mariani et al, 2017). The binding partner of GABPA, METTL23, has been reported to play an essential role in human cognition (Reiff et al, 2014).…”
Section: Discussionmentioning
confidence: 99%